2020
DOI: 10.1016/j.arth.2020.02.063
|View full text |Cite
|
Sign up to set email alerts
|

Reimbursement and Complications in Outpatient vs Inpatient Unicompartmental Arthroplasty

Abstract: unicompartmental knee arthroplasty outpatient inpatient reimbursement cost complications a b s t r a c tBackground: Increasing utilization of unicompartmental knee arthroplasty (UKA) has driven a greater push for outpatient treatment and cost containment in the setting of bundled payments. The purpose of this study is to evaluate utilization trends of inpatient vs outpatient UKA, index episode and 90-day reimbursement, and any differences in medical or surgical complications. Methods: The PearlDiver database w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Outpatient surgeries account for 60–70% of all surgical procedures [ 6 , 7 ]. In addition, more complex surgeries (e.g., total knee arthroplasty, thyroidectomy, hysterectomy) with greater risks of VTEs are currently being performed in ambulatory facilities [ [8] , [9] , [10] ]. Increased surgical duration has been demonstrated to be an independent risk for the development of VTE after inpatient surgeries [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Outpatient surgeries account for 60–70% of all surgical procedures [ 6 , 7 ]. In addition, more complex surgeries (e.g., total knee arthroplasty, thyroidectomy, hysterectomy) with greater risks of VTEs are currently being performed in ambulatory facilities [ [8] , [9] , [10] ]. Increased surgical duration has been demonstrated to be an independent risk for the development of VTE after inpatient surgeries [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to total knee arthroplasty (TKA), unicompartmental knee arthroplasty (UKA) is associated with an earlier recovery, less postoperative pain, lower morbidity and mortality, and a greater "feel" of a normal knee, which made UKA a better surgical option for patients with end-stage medial compartment osteoarthritis [15] [16]. Because of not increasing postoperative complications and risk of re-admission, outpatient joint arthroplasty have been widely performed in recent years [17].…”
Section: Discussionmentioning
confidence: 99%
“…A shorter LOS could effectively save the cost of hospitalization and reduce the risk of nosocomial infection [18]. Current studies have con rmed the safety and e cacy of outpatient UKA [7][9] [13]. Meanwhile, excellent anesthesia and intraoperative monitoring were necessary for ensuring the safety and e cacy of the operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The development of protocols for transitioning from outpatient to inpatient orthopedic procedures has seen tremendous success for various orthopedic procedures, such as total joint arthroplasty. [13][14][15][16][17][18] These studies have found ambulatory surgery to be safe and effective and may potentially result in a reduction of nosocomial complications when compared to inpatient procedures.…”
Section: Introductionmentioning
confidence: 99%